Strategies to decolonize uropathogens in urethra and bladder for prevention of urinary tract infections among pregnant women: A comprehensive narrative analysis - Mohd Afzal; Abhishek Sharma; Ashok Kumar Sah; Aksh Chahal (Urological Science)
Urinary tract infections (UTIs) are frequent among pregnant women and can cause difficulties for both mother and fetus. Uropathogens that colonize the urethra and bladder are significant contributors to UTIs during pregnancy. Preventive measures aimed at uropathogen decontamination have emerged as promising options for reducing UTI incidence in this population. This comprehensive narrative analysis synthesized evidence from published literature to explore preventive measures for decolonizing uropathogens in the urethra and bladder among pregnant women. Key databases including PubMed, MEDLINE, Web of Science, Cochrane Library, Scopus, and Google Scholar were searched using relevant keywords such as “urinary tract infections,” “pregnancy,” “decolonization,” and “uropathogens.” Primary preventative measures for uropathogen decolonization in pregnant women include antimicrobials such as nitrofurantoin and cephalexin, probiotics including Lactobacillus species, and behavioral changes such as increased fluid intake and good hygiene. While effective, concerns about antimicrobial resistance and long-term use require careful consideration and monitoring. The ideal length and frequency of these therapies are now being investigated by researchers. Uropathogen decontamination has the potential to reduce UTI incidence and improve mother and newborn health. It is critical to tailor evidence-based treatments to the specific requirements of pregnant women in prenatal care settings. Preventive interventions aimed at uropathogen decontamination, such as antibacterial medications, probiotics, and behavioral changes, are potential options for lowering UTI incidence in pregnant women. However, further study is required to improve methods, overcome obstacles, and assess long-term effects.